Microleakage in posterior teeth with different materials and different types of cavities - Everton Ribeiro dos Santos; Adair Luis Busato (Wolters Kluwer Medknow Publications, 2019)
Background: The purpose of this study was to investigate the behavior of a resin-based 2,2-bis (p-[2'-hydroxy-3'-methacryloxypropoxy] phenylene) propane and a composite resin modified with oxirane, regarding the ability of marginal sealing, both with direct restorations and indirect restorations. Materials and Methods: To achieve this, mesio- and disto-occlusal cavities were made on the same tooth, totalling 100 cavities. These cavities were restored with two materials, Filtek P90 (3M ESPE) and Opallis (FGM). Then, they were divided into two groups: Fifty direct restorations, each sample restored with the two materials, following the manufacturer's protocol and fifty indirect restorations, and then cemented with a paste obtained by diluting the resin in its adhesive. The templates were thermally cycled, 30 s at 5°C and 30 s at 55°C for 500 cycles and then were immersed in methylene blue for 24 h. Afterward, they were trimmed using a plaster trimmer from occlusal toward a gingival direction. These samples were analyzed with stereomicroscope (×3) by two blinded observers. Then, a system which considers the average number of surrounding walls that have suffered infiltration on a scale of 0-3 was used. Results: Data were subjected to statistical analysis (Mann-Whitney and Kruskal-Wallis tests) with a significance level of 5% maximum. Conclusion: It was concluded that the indirect restorations showed the greatest number of restorations with score 0 and 1 (34) and lowest score 2 and 3 (16). This suggests that indirect restorations regardless of the material used behaved more effectively regarding the marginal sealing of restorations.